Effectiveness of Emotional Regulation Training on Parenting Style Related to Parental Obesity and Weight Management in Adolescents with Bulimia Nervosa - Sadeghzadeh, Rozita; Sheibeh, Zohreh; Solat, Farya; Naeiji, Mohamad Reza; Mirzai, Fatemeh; Damavandi, Mahta (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: Eating disorders are among the common mental/psychosomatic disorders that cause numerous problems in physical health, psychological functioning, and the quality of life of adolescents. The aim of the present study was to determine the effectiveness of emotional regulation training on the parenting style related to parental obesity and weight management in adolescents with Bulimia Nervosa. Materials and Methods: The current study was a quasi-experimental research with a pre-test, post-test, and control group design. It included adolescents with Bulimia Nervosa and a body mass index above 25 who were referred to comprehensive health service centers in District 7 of Tehran in 2023. The statistical sample consisted of 30 individuals who were randomly divided into two groups of 15, an experimental group and a control group, using random allocation. The intervention group received emotional regulation training in 8 sessions lasting 75 minutes once a week. Data were collected using the Parenting Style Questionnaire (Baumrind, 1973) and the Weight Management Self-Efficacy Questionnaire (Clark et al., 1991). Multivariate analysis of covariance and SPSS software version 22 were used for data analysis. Findings: The results showed that emotional regulation training was effective on the parenting style related to parental obesity (P<0.001) and weight management (P<0.001) in adolescents with Bulimia Nervosa. Conclusion: Based on the current findings, it can be concluded that emotional regulation training for parents leads to changes and improvements in weight management in adolescents with Bulimia Nervosa.